Late Renal Allograft Rupture Associated with Cessation of Immunosuppression following Graft Failure - Sumayah Askandarani; Noura Aloudah; Hanan Al Enazi; Khaled O. Alsaad; Abdulrahman Altamimi (Case Reports in Transplantation)
A 29-year-old man developed chronic allograft nephropathy 63 months after renal transplantation. He became symptomatic with advanced chronic graft failure; his immunosuppressive medications were reduced and he was commenced on haemodialysis. Two months following the withdrawal of immunosuppression, he presented with abdominal pain, haematuria, and a marked drop in haemoglobin. The patient was taken to the operating room, where the renal allograft was found to be ruptured, and graft nephrectomy was subsequently performed. Histological examination of the graft specimen showed severe haemorrhagic acute vascular cellular rejection in a background of marked chronic allograft vasculopathy. Immunostaining for C4d showed diffuse, strong, linear circumferential staining of the peritubular capillaries, indicating a concurrent antibody-mediated rejection. We report herein an unusual case of spontaneous renal allograft rupture that occurred long time after transplantation due to severe acute rejection following cessation of immunosuppressive medications for advanced chronic allograft failure. To the best of our knowledge, the time interval between transplantation and the rupture of this allograft is the longest of those reported in the literature.